URB597 and Andrographolide Improve Brain Microvascular Endothelial Cell Permeability and Apoptosis by Reducing Oxidative Stress and Inflammation Associated with Activation of Nrf2 Signaling in Oxygen-Glucose Deprivation - Wang, Da-Peng; Kang, Kai; Sun, Jun; Lin, Qi; Lv, Qiao-Li; Hai, Jian (Oxidative medicine and cellular longevity, 2022)
Ischemic stroke, a cerebrovascular disease worldwide, triggers a cascade of pathophysiological events, including blood-brain barrier (BBB) breakdown. Brain microvascular endothelial cells (BMECs) play a vital role in maintaining BBB function. The injury of BMECs may worsen neurovascular dysfunction and patients’ prognosis. Therefore, uncover the principal molecular mechanisms involved in BBB disruption in stroke becomes pressing. The endocannabinoid system (ECS) has been implicated in increasingly physiological functions, both in neurometabolism and cerebrovascular regulation. Modulating its activities by the fatty acid amide hydrolase (FAAH) shows anti-inflammatory characteristics. Andrographolide (AG), one Chinese herbal ingredient, has also attracted attention for its role in immunomodulatory and as a therapeutic target in BBB disorders. Recently, the FAAH inhibitor URB597 and AG have important regulatory effects on neuronal and vascular cells in ischemia. However, the effects of URB597 and AG on BMEC permeability and apoptosis in oxygen-glucose deprivation (OGD) and the underlying mechanisms remain unclear. To address these issues, cultured BMECs (bEnd.3 cells) were exposed to OGD. The cell viability, permeability, tube formation, and apoptosis were assessed following treatment with URB597, AG, and cotreatment. Mitochondrial membrane potential (MMP), reactive oxygen species (ROS), superoxide dismutase (SOD), catalase (CAT), malondialdehyde (MDA), proinflammatory factors, tight junction (TJ) proteins, and oxidative stress-mediated Nrf2 signaling were also investigated. Results revealed that OGD broke the endothelial barrier, cell viability, MMP, and tube formation, which was reversed by URB597 and AG. OGD-induced enhancement of ROS, MDA, and apoptosis was reduced after drug interventions. URB597 and AG exhibited antioxidant/anti-inflammatory and mitochondrial protective effects by activating Nrf2 signaling. These findings indicated that URB597 and AG protect BMECs against OGD-induced endothelial permeability impairment and apoptosis by reducing mitochondrial oxidative stress and inflammation associated with activation of Nrf2 signaling. URB597 and AG showing the vascular protection may have therapeutic potential for the BBB damage in ischemic cerebrovascular diseases.